Three randomized studies of dentine hypersensitivity reduction after short‐term SnF2 toothpaste use. (2nd September 2019) - Creeth, Jonathan; Maclure, Robert; Seong, Joon; Gomez‐Pereira, Paola; Budhawant, Chandrashekhar; Sufi, Farzana; Holt, Jonathan; Chapman, Nicholas; West, Nicola
Abstract: Aim: To evaluate effects of a 0.454% stannous fluoride test toothpaste on dentine hypersensitivity (DH) applied by fingertip, then 3 days' brushing, versus a sodium monofluorophosphate‐based control. Materials and Methods: In three randomized clinical studies, DH was assessed using evaporative (Schiff scale) and tactile (Yeaple probe) stimuli. Participants applied toothpaste to two sensitive teeth by fingertip (60 s each); DH was re‐assessed, prior to brushing. Test treatment participants brushed their sensitive teeth, with all participants then brushing all teeth for ≥60 s, twice daily for 3 days. DH was re‐assessed. Data were analysed by study and then pooled. Results: In two studies, test treatment significantly reduced DH versus control treatment after fingertip application and 3 days' brushing (both measures). In one study, both treatments significantly reduced DH without between‐treatment differences. Mean Schiff differences (95% confidence intervals) for fingertip/3d were as follows: Study 1: −0.09 (−0.280, 0.092)/ −0.18 (−0.442, 0.072); Study 2: −0.72 (−0.839, −0.610)/ −1.02 (−1.150, −0.882); and Study 3: −0.26 (−0.387, −0.123)/ −0.92 (−1.055, −0.793). Pooled analysis indicated test treatment significantly reduced DH versus control (both timepoints, both measures). Toothpastes were generally well‐tolerated. Conclusion: Studies indicated that single, fingertip application of a SnF2 toothpaste reduced DH versus a control. DH relief increased over 3 days.